Perceived Usefulness of Fintech, Lifestyle Orientation, and Consumptive Behaviour: Evidence from Bekasi Regency - Deswita Aryanti; Rina Mutiara (Lentera Ilmu Nusantara, 2026)
The digital economy has intensified interest in understanding how fintech adoption and lifestyle orientation influence individual consumption patterns. In the context of Bekasi Regency, the increasing use of digital financial services and the growing influence of contemporary lifestyle preferences may reshape the way individuals engage in consumption. This study aims to analyze the effect of perceived usefulness of fintech and lifestyle orientation on consumptive behavior in Bekasi Regency. A quantitative approach was employed to examine the relationships among variables. The population comprised the community in Bekasi Regency, and the sample size was determined using the Hair formula, resulting in 160 respondents. Data were collected through observation, literature study, and questionnaires, and were analyzed using Smart PLS. The results indicate that perceived usefulness of fintech positively affects consumptive behavior, and lifestyle orientation also has a positive effect on consumptive behavior. These findings highlight that fintech is not merely perceived as a functional financial tool, but may also encourage consumption when its utility aligns with lifestyle-driven preferences. This study enriches the literature on digital financial behavior by showing that technological and behavioral factors jointly influence consumptive behavior, while also underlining the importance of financial literacy in the digital era.